This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: ECE 580 / Math 587 SPRING 2011 Correspondence # 3 February 3, 2011 Solution Set 1 1. Let x ∈ M + N . Then x = m + n with m ∈ M , n ∈ N . Clearly m ∈ M ∪ N , n ∈ M ∪ N and x = m + n ∈ [ M ∪ N ]. Thus M + N ⊂ [ M ∪ N ]. Let x ∈ [ M ∪ N ]. Then x = ∑ k i =1 d i y i with y i ∈ M or y i ∈ N (or both). Thus x = m + n , where m = ∑ y i ∈ M ∪ e N d i y i ∈ M n = ∑ y i ∈ N d i y i ∈ N. Thus [ M ∪ N ] ⊂ M + N , and combined with above we have equality. 2. We must show that (i) K ⊂ co ( S ) (ii) K ⊃ co ( S ) (i) K ⊂ co ( S ) k ∈ K ⇒ k = m ∑ i =1 α i x i , where m ∑ i =1 α i = 1 , α i > ,x i ∈ S. Now x i ∈ S ⇒ x i ∈ co ( S ) . co ( S ) convex ⇒ α 1 x 1 α 1 + α 2 + α 2 x 2 α 1 + α 2 = y 1 ∈ co ( S ) . Similarly, α 1 + α 2 α 1 + α 2 + α 3 y 1 + α 3 x 3 α 1 + α 2 + α 3 = y 2 ∈ co ( S ) . But y 2 = α 1 x 1 α 1 + α 2 + α 3 + α 2 x 2 α 1 + α 2 + α 3 + α 3 x 3 α 1 + α 2 + α 3 . Continuing in this manner, and noting that ∑ n i =1 α i = 1, y n − 1 = α 1 x 1 ∑ n i =1 α i + ··· + α n x n ∑ n i =1 α i = n ∑ i =1 α i x i ∈ co ( S ) . Therefore, K ⊂ co ( S ) . (ii) co ( S ) ⊂ K ∀ x,y ∈ K ∃ α i ,x i ,α ′ i ,x ′ i : x = n ∑ i =1 α i x i and y = n ∑ i =1 α ′ i x ′ i where n ∑ i =1 α i = n ∑ i =1 α ′ i = 1 . Now, for 0 < λ < 1, λy + (1 − λ ) x = λ n ∑ i =1 α ′ i x ′ i + (1 − λ ) n ∑ i =1 α i x i where λ n ∑ i =1 α ′ i + (1 − λ ) n ∑ i =1 α i = 1 . = ⇒ λy +(1 − λ ) x ∈ K . Therefore, K is convex. Obviously S ⊂ K , and hence co ( S ) ⊂ K by definition. 3. By H¨older’s inequality, for x ∈ L p [ − 1 , 1] and y ∈ L q [ − 1 , 1], with (1 /p ) + (1 /q ) = 1, we have ∫ 1 − 1  x ( t ) y ( t )  dt ≤ ∥ x ∥ p ∥ y ∥ q with equality if, and only if,  x ( t )  = (  y ( t )  ∥ y ∥ q ) q p ∥ x ∥ p Now, for the problem at hand, take y ( t ) = t 3 and p = 3, which makes q = 3 / 2. Furthermore, ∥ x ∥ p = 2 1 3 . Hence, from H¨older’s inequality, ∫ 1 − 1  x ( t ) t 3  dt ≤ 2 1 3 ∥ t 3 ∥ 3 2 = (2) 5 3 (11) − 2 3 , which says that ∫ 1 − 1  x ( t ) t 3  dt cannot be larger than (2) 5 3 (11) − 2 3 , and in fact this upper bound can be achieved (from the equality above) by choosing  x ( t )  = (  t 3  (2) − 4 3 (11) 2 3 ) 1 2 2 1 3 = (2) − 1 3 (11) 1 3  t  3 2 2 Now, ∫ 1 − 1 t 3 x ( t ) dt ≤ ∫ 1 − 1  t 3 x ( t )  dt where we would have equality if x ( t ) is picked so that t 3 x ( t ) is equal to  t 3 x ( t )  , that is the sign of x ( t ) should be the same as the sign of t 3 , and hence of t . Hence, the unique solution to the maximization problem is x ( t ) = ( 2 ) − 1 3 ( 11 ) 1 3  t  3 2 sgn ( t ) 4. Noting the obvious relationship, min ∫ 1 − 1 t 3 x ( t ) dt ≥ min ( − ∫ 1 − 1  t 3 x ( t )  dt ) = − max ∫ 1 − 1  t 3 x ( t )  dt it readily follows from the solution to Problem 3 above that the following choice of...
View
Full
Document
This note was uploaded on 10/11/2011 for the course ECE 580 taught by Professor Staff during the Spring '08 term at University of Illinois, Urbana Champaign.
 Spring '08
 Staff

Click to edit the document details